EFFECT OF STRETCHING EXERCISES ON THE PERFORMANCE OF 100 METER FEMALE NOVICE HURDLES - Devi, Suneeta; Kumar, Dr Arun (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
Objectives of the study were to find out the effect of stretching exercises on the performance of 100 meter. Female athletes. For that purpose 30 female athletes from Bhatinda district of Punjab were selected with the help of simple random sampling method.  Sample was divided in to two groups i.e. experimental and control group. Given training programme was provided to experimental group where as peusodo training was given to control group. Pre test was taken before starting the training programme. After three weeks a mid test was taken to know the effectiveness of training programme. After six week post test was taken and it was found that significant difference found in pre and post teat of both the group i.e. control and experimental group.